Comparative Effectiveness of Etoricoxib and Diclofenac Sodium in Improving Quality of Life Among Osteoarthritis Patients - Nurmesa, Adi; Putra, Dimas Setyadi (RSUP Dr. Kariadi, 2026)
BACKGROUND : The effectiveness of etoricoxib versus diclofenac in outpatiens with pain due to osteoarthritis is unclear. There is still debate regarding the relative effectiveness and safety between both in improving the quality of life of OA patients AIMS :To assess the effectiveness of etoricoxib compared to diclofenac by assessing the quality of life outcomes of Osteoarthritis patients using instruments such as the EQ-5D-5L. METHOD : Study design using a cross-sectional study design by looking at the results of the quality of life of patients using NSAIDs in the form of diclofenac sodium and etoricoxib. RESULT : The results showed that moderate positive correlation between etoricoxib or diclofenac sodium therapy in OA patients decreasing utility value ( 0.294; 95% CI = 0.098 - 0.467; p = 0.003). A strong positive correlation was shown between etoricoxib or sodium therapy in OA patients and VAS ( 0.558; 95% CI = 0.402 - 0.682; p = <0.000). These results indicate that each therapeutic use of etoricoxib or diclofenac sodium can improve the utility value or VAS, or conversely. CONCLUSION : The quality of life value of etoricoxib is better than diclofenac sodium, which is 0.924 and there is a positive correlation between the use of etoricoxib and diclofenac sodium in improving quality of life and VAS values in osteoarthritis patients.